### Related

##### lhs-rhs-sqrt

lhs : ( - sqrt(3) ) *...

rhs : 4 - 3 * x;

locus : lhs - rhs = 0;

Calculate

##### lhs-linsolve-plot2d

eq1:x*4+y-2=y;

eq2:x+2=y;

linsolve([eq1,eq2],[x...

Calculate

a_12xm[t]:=(N_x[t]-N_...

eq:a_12xm[t]=(13+11*D...

Calculate

##### lhs-rhs-sqrt

g:sqrt(x-3)-1=0 /* E...

g2:lhs(g1)**2=rhs(g1)...

Calculate

AwP_xm[t]:=(M__x[t]-M...

V[t]:=12*awi_12xm[0]/...

Calculate

##### lhs

lhs(3*x^2+2*x+x^3-x^2...

Calculate

a4:81;

a7:2187;

g1:81=a1+q^3;

Calculate

e=12;

lhs(e);

Calculate

##### lhs-linsolve

eq1:x*4+y-2=y;

eq2:x+2=y;

linsolve([eq1,eq2],[x...

Calculate

##### lhs-subst

var1: E[A] = 1.0e7;

var2: E[P] = 3.04e5;

var3: R[1] = .62;

Calculate

### lhs

Run Example
(%i1)rt:tan(atan(1/2)+atan(1/3))=1;
1         1
(%o1)                     tan(atan(-) + atan(-)) = 1
2         3
(%i2) trigsimp(lhs(rt));
1         1
sin(atan(-) + atan(-))
2         3
(%o2)                       ----------------------
1         1
cos(atan(-) + atan(-))
2         3
(%i3)  logarc(lhs(rt));
%i                %i             %i                %i
%i (log(-- + 1) - log(1 - --))   %i (log(-- + 1) - log(1 - --))
2                 2              3                 3
(%o3) - tan(------------------------------ + ------------------------------)
2                                2
(%i4) ratsimp(%);
(%o4)
Run Example
eq:(x^2-17*x+1)^(x^2-34*x+1)=1;
2
2            x  - 34 x + 1
(%o1)                  (x  - 17 x + 1)              = 1
(%i2) ratdisp:false;
(%o2)                                false
(%i3) ratsimpexpons:false;
(%o3)                                false
(%i4) rat(lhs(eq)), ratsimp;
2
2            x  - 34 x + 1
(%o4)                    (x  - 17 x + 1)
(%i5)
Run Example
derivabbrev:true ;
(%o1)                                true
(%i2) x(t):= r(t)*sin(theta(t));
(%o2)                     x(t) := r(t) sin(theta(t))
(%i3) y(t):=r(t)*cos(theta(t));
(%o3)                     y(t) := r(t) cos(theta(t))
(%i4) xdot: diff(x(t), t, 1);
(%o4)         r(t) cos(theta(t)) theta(t)  + r(t)  sin(theta(t))
t       t
(%i5) ydot: diff(y(t), t, 1);
(%o5)         r(t)  cos(theta(t)) - r(t) sin(theta(t)) theta(t)
t                                            t
(%i6) xdotdot: diff(xdot, t, 1);
2
(%o6) r(t) cos(theta(t)) theta(t)    - r(t) sin(theta(t)) (theta(t) )
t t                               t
+ 2 r(t)  cos(theta(t)) theta(t)  + r(t)    sin(theta(t))
t                       t       t t
(%i7) ydotdot: diff(ydot, t, 1);
2
(%o7) - r(t) sin(theta(t)) theta(t)    - r(t) cos(theta(t)) (theta(t) )
t t                               t
- 2 r(t)  sin(theta(t)) theta(t)  + r(t)    cos(theta(t))
t                       t       t t
(%i8) Assumption1: xdotdot=0;
2
(%o8) r(t) cos(theta(t)) theta(t)    - r(t) sin(theta(t)) (theta(t) )
t t                               t
+ 2 r(t)  cos(theta(t)) theta(t)  + r(t)    sin(theta(t)) = 0
t                       t       t t
(%i9) Assumption2: ydotdot=0;
2
(%o9) - r(t) sin(theta(t)) theta(t)    - r(t) cos(theta(t)) (theta(t) )
t t                               t
- 2 r(t)  sin(theta(t)) theta(t)  + r(t)    cos(theta(t)) = 0
t                       t       t t
(%i10) E1: solve(Assumption1, r(t));
sin(theta(t)) r(t)    + 2 cos(theta(t)) theta(t)  r(t)
t t                           t     t
(%o10) [r(t) = - -------------------------------------------------------]
2
cos(theta(t)) theta(t)    - sin(theta(t)) (theta(t) )
t t                          t
(%i11) E2: solve(Assumption2, r(t));
cos(theta(t)) r(t)    - 2 sin(theta(t)) theta(t)  r(t)
t t                           t     t
(%o11) [r(t) = -------------------------------------------------------]
2
sin(theta(t)) theta(t)    + cos(theta(t)) (theta(t) )
t t                          t
(%i12) solve(subst(E2, [E1]), r(t));
(%o12)                                []
(%i13) E3: solve(lhs(E1)-lhs(E2), r(t));
3
2 (theta(t) )  r(t)
t       t
(%o13)                [r(t)    = - --------------------]
t t         theta(t)
t t
(%i14)

Help for Lhs